Role of community pharmacy and pharmacists in self-care in Brazil - Rotta, Inajara (2023)
Global healthcare systems, including the National Health System in Brazil - one of the largest public models in the world -, continue to evolve, as well as populations' health needs, currently shaped by individuals feeling a greater desire to manage their own health. Self-care practices are part of several public policies and clinical guidelines in Brazil including the National Policy on Complementary and Integrative Practices, the National AIDS Control Program, the National Policy for Women's Health, and the Guidelines for Care of People with Chronic Diseases. There are over 100,700 community pharmacies, in the country (89.2% privately owned) employing 234,300 pharmacists, representing an important delivery point for self-care, as they are the first point of access to care for most patients. Self-medication is a common practice in Brazil (prevalence rates of self-medication ranging from 16.1% to 35.0%), especially with non-prescription/over-the-counter medicinal products (65.0%). In fact, these products represent over 25% of the volume marketed of medicines, summing revenues of USD 1.9 billion per year. Studies demonstrated a positive budget impact as important savings for the National Health System due to reductions in unnecessary medical appointments and loss of working days. In addition to minor ailments management, other self-care services provided by community pharmacies that are frequently sought by Brazilian citizens (20-25% of cases) are smoking cessation and weight management (costs per service ranging from around USD 5.00-12.00). However, pharmacy services are not yet as fully integrated in Brazil to the same extent as in other countries. Barriers such as standardization of processes (from services' design, implementation, and evaluation in practice), pharmacist remuneration for the provision of services and the amount to be charged for the service are still a matter of controversy. For more rapid and sustainable advances in these practices, communication among various stakeholders, professional practice and healthcare regulations, standardization of services, and financing of self-care (both publicly and privately) are urgently needed. This paper provides an overview of some self-care services provided by community pharmacies in Brazil and calls attention to the ongoing challenges to move the National Health system forward.